Influence of Intrinsic Motivation and Parenting Style on Stability Personality of College Students at Defense University - Tri Panca Arbiansyah; Sri Iswati (Applied Quantitative Analysis, 2025)
This study examines the influence of intrinsic motivation and parenting style on personality stability among students at the Defense University. Personality stability is a crucial component in shaping resilient, consistent, and adaptive character, especially in a military educational environment that demands a high level of discipline. Intrinsic motivation is defined as the internal drive to engage in activities perceived as meaningful, enjoyable, and challenging. Meanwhile, parenting style, whether delivered by regimental caregivers or peer mentors (senior cadets), plays a vital role in shaping the attitudes and behaviors of students. Emotional stability reflects an individual's ability to process and express their emotions in a manner consistent with their developmental stage. This research employed a quantitative approach using a multiple linear regression design. The population consisted of 250 students, with 153 active students selected as the sample. Data were collected using a Likert-scale questionnaire that measured the variables of intrinsic motivation, parenting style, and personality stability. The findings revealed that intrinsic motivation and parenting style simultaneously significantly influence personality stability, with a standardized coefficient of 0.83 and a t-value of 18.59. Intrinsic motivation alone had a significant effect, with a coefficient of 0.71 and a t-value of 12.29, whereas parenting style had a significant effect, with a coefficient of 0.18 and a t-value of 3.23. These results reinforce the importance of autonomy, competence, and relatedness, and support the two-dimensional parenting theory. The study also highlights the significant roles of permissive and authoritarian parenting styles within the military university context. This research provides theoretical contributions to the development of personality and motivation in higher education, particularly in military academic environments. The findings serve as a basis for institutions to design learning strategies and character-building programs that promote intrinsic motivation and support the development of a stable personality. This study also provides a foundation for future psychosocial interventions and initiatives aimed at enhancing student character.